A Consumer Perception Research on the Subject of a New Technology in a Developing Dynamic Market: 3G Technology in Turkey - Atici, Bunyamin; Bati, Ugur (Igi Global, 2011)
The amount of demand for new products like 3G is related to adoption and spread of innovations. Research suggests that innovativeness is related to consumer behavior and characteristics. Research shows that new technologies like 3G are not evaluated by only its functional sides in the consumer perception. Consumers also perceive symbolic sides to this type of technology. This study measures the interests of the population that live in the urban area of Turkey and economically active and working for the 3G technology, their product purchasing criteria, product using habits, brand recognition levels, brand preferences, and tendencies for purchasing products and services in the near future. The research is performed with the participation of 612 persons in 12 provinces. The demographic characteristics belonging to the consumers who participate in the survey study, the reliability analysis results concerning the scale, t test, factor analysis, frequency analysis, correlation analysis, and variance analyses are performed in this chapter of the research. Findings show that the dynamic Turkish consumer gives significant importance to this new technology as functional and symbolic.
Keywords: 3G; Cell Phone; Consumer Perception; Technology; Technology Adoption